2005
DOI: 10.1071/ar04094
|View full text |Cite
|
Sign up to set email alerts
|

The influence of girdling on flower type, number, inflorescence density, fruit set, and yields in three different olive cultivars (Barnea, Picual, and Souri)

Abstract: The influence of girdling on flower type and number, inflorescence density, and fruit set in 3 different olive cultivars (Barnea, Picual, and Souri) under intensive growing conditions using saline irrigation water was studied for 3 years. The density of inflorescences on the branches was not affected by girdling in any of the 3 cultivars during any of the 3 consecutive years studied. Also, no clear relation between the number of flowers and girdling was found in any of the 3 cultivars tested. The percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…Healing of the wounds produced by girdling was satisfactory in 'Grappolo 541' and 'Ascolano 315' plants and occurred immediately after the cut, corroborating LÓPEZ-RIVARES & GARCÍA (1990), who observed better healing of the wounds made in March and April in "Manzanilla" plants. Good healing of plants of the Maria da Fé variety was not observed, as some branches of this variety were dried out, with the presence of yellowed leaves.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Healing of the wounds produced by girdling was satisfactory in 'Grappolo 541' and 'Ascolano 315' plants and occurred immediately after the cut, corroborating LÓPEZ-RIVARES & GARCÍA (1990), who observed better healing of the wounds made in March and April in "Manzanilla" plants. Good healing of plants of the Maria da Fé variety was not observed, as some branches of this variety were dried out, with the presence of yellowed leaves.…”
Section: Resultssupporting
confidence: 63%
“…In olive trees, studies show superior results with an increase of 50 per cent in flowering in low harvest years (off years) (LEVIN & LAVEE 2005) and a significant effect on production with successive girdlings (EL KHAWAGA 2007, AHMAD et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Although the results are considered preliminary, owing to the juvenile state of the assay, this result should be considered in the subsequent evaluations of the assay, given that according to Levin and Lavee (2005) alternate bearing is still a serious problem in the cultivation of numerous fruit species, including olives, which consequently must be managed in order to minimize the adverse effects on production (Tapia et al, 2006). Unlike PML and PA03-07, ABI did not present significant differences among the 10 best varieties (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, NAA effects might be due to that to an improve of the internal hormonal and carbohydrate level of the canopy which is responsible for improving number of inflorescence (Levin and Lavee, 2005), flower number (Noor et al, 1995) fruit setting and fruit size in Kalamata olive cv. (Proietti &Tombesi, 1990 andPetrisou andVoyiatzis, 1994).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Meanwhile, NAA (mg. l -1 ) increased significantly fruit weight; in addition the control increased significantly seed length and weight during 2011 and 2012 seasons. Noor et al (1995), Mistra & Datta, (2001) and Levin & Lavee, (2005) reported that NAA improved number of inflorescence flower number fruit setting and fruit size.…”
Section: Number Of Fruits/m and Fruit Drop Percentagementioning
confidence: 99%